2023
DOI: 10.29133/yyutbd.1124458
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Vermicompost, Compost and Animal Manure on Vegetative Growth, Physiological and Antioxidant Activity Characteristics of Thymus vulgaris L. under Water Stress

Abstract: This study investigated the effect of organic fertilizers on vegetative growth and the physiological and antioxidant activity characteristics of thyme plants grown under stress. A factorial experiment was conducted according to randomized complete block design with 12 combinations and 3 replications in the 2018 growing season. The experiment factors were the implementation of organic fertilizers at 4 levels (vermicompost, manure compost, animal manure, and control) and irrigation regime at 3 levels (Irr1, Irr2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 39 publications
0
6
0
Order By: Relevance
“…Reduced growth and root activity, coupled with increased evaporation and transpiration from the crop area, have been reported as important factors contributing to the decline in RWC [ 8 ]. The decrease in leaf RWC due to severe irrigation regimes is primarily due to the reduced water absorption by the roots and increased water transpiration through the leaves, ultimately leading to the closure of leaf stomata [ 31 ]. The decline in the plant tissue turgor and RWC can represent an initial sign of stress having a direct influence on cell division and size [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Reduced growth and root activity, coupled with increased evaporation and transpiration from the crop area, have been reported as important factors contributing to the decline in RWC [ 8 ]. The decrease in leaf RWC due to severe irrigation regimes is primarily due to the reduced water absorption by the roots and increased water transpiration through the leaves, ultimately leading to the closure of leaf stomata [ 31 ]. The decline in the plant tissue turgor and RWC can represent an initial sign of stress having a direct influence on cell division and size [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…When soil water availability is limited, the uptake of water, the solubility of nutrients in the soil, and their absorption by the roots decrease with negative consequences on photosynthesis and transpiration rates [ 9 , 31 ]. Consequently, plants reduce their growth to compensate for the water deficiency and lack of nutrients as observed in thyme plants under water stress [ 9 , 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…It is common for plant yield to decrease under drought conditions. Many studies have reported reductions in plant yield or biomass due to drought stress ( Chrysargyris et al, 2016 ; Aslani et al, 2023 ; Celikcan, Kocak & Kulak, 2021 ; Rahimi et al, 2023a , 2023b ; Abdi et al, 2018 ; Karimi et al, 2020 ). There are multiple mechanisms for drought stress to significantly decreases plant yield and biomass.…”
Section: Discussionmentioning
confidence: 99%
“…severe stress conditions. Generally, it is expected that chlorophyll levels decrease with stress, as many studies report reductions in chlorophyll under drought conditions ( Aslani et al, 2023 ; Rahimi et al, 2023a , 2023b , Imani et al, 2023 ). However, there are also few other studies suggests opposite that chlorophyll increases under drought stress ( Mulugeta, Sárosi & Radácsi, 2023 ; Emami Bistgani et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…The efficiency of water use is closely linked to the effectiveness of the use of precipitation since there is no other water source, especially in arid and semi-arid zones of the world where RUE had a stable value of ≈ 4 kg of dry matter ha -1 mm -1 rainfall (Varvel, 1995;Hatfield et al, 2001). Understanding RUE is critical in addressing the challenges of climate change, food security, and environmental degradation (associated with indiscriminate nitrogen fertilizer use) from both socioeconomic and technological perspectives (Zhang et al, 2015;Rahimi et al, 2023).…”
Section: Introduction Introduction Introduction Introductionmentioning
confidence: 99%